1985
DOI: 10.1113/jphysiol.1985.sp015870
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate at the onset of static exercise in man with partial neuromuscular blockade.

Abstract: In human subjects the length of the first complete cardiac cycle after the onset of static finger or hand muscle contractions was recorded. Graded contractions as well as maximal contractions in which muscle fatigue was provoked by ischaemia were studied. Maximal finger muscle contractions were also weakened by partial neuromuscular blockade with either decamethonium or tubocurarine. The change in R‐R interval at the onset of exercise was variable and in part dependent on the length of the last R‐R interval be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
31
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 23 publications
5
31
0
Order By: Relevance
“…Therefore, most probably, the handgrip may have been initiated less vigorously than the onset of one-leg knee extension. Thus, maximal handgrip is usually associated with an immediate approximately 9 % increase in heart rate while submaximal contractions show a smaller or no increase in heart rate over the first cardiac cycle after the onset of the contraction (Secher, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, most probably, the handgrip may have been initiated less vigorously than the onset of one-leg knee extension. Thus, maximal handgrip is usually associated with an immediate approximately 9 % increase in heart rate while submaximal contractions show a smaller or no increase in heart rate over the first cardiac cycle after the onset of the contraction (Secher, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…At the onset of a strong isometric (static) muscle contraction, heart rate increases and even the first heart beat comes faster (Hollander, 1975;Secher, 1985;Iwamoto, Mitchell, Mizuno & Secher, 1987). Vagal withdrawal is the efferent limb of this initial heart rate response (Freyschuss, 1970;Hollander, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…However, in experimental models in which one of the components is increased or decreased, the other may produce a near appropriate cardiovascular response. For example, some studies have emphasized the importance of the central neural component (Freyschuss, 1970;Goodwin, McCloskey & Mitchell, 1972;Schibye, Mitchell, Payne & Saltin, 1981;Secher, 1985;Leonard et al 1985) and others have emphasized the importance of the reflex neural component (Alam & Smirk, 1937;Hultgren & Sj6holm, 1982). Also animal studies have shown that cardiovascular responses similar to those occurring during exercise can be produced by either central or reflex neural mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Heart rate and mean arterial pressure increase immediately at the onset of static exercise (Freyschuss, 1970;Hollander, 1975;Secher, 1985;Iwamoto, Mitchell, Mizuno & Secher, 1987;Lassen, Mitchell, Reeves, Rogers & Secher, 1989). Two neural mechanisms have been considered to explain this instantaneous increase in heart rate.…”
Section: Introductionmentioning
confidence: 99%